2012
DOI: 10.2147/aabc.s30620
|View full text |Cite
|
Sign up to set email alerts
|

B-Pred, a structure based B-cell epitopes prediction server

Abstract: The ability to predict immunogenic regions in selected proteins by in-silico methods has broad implications, such as allowing a quick selection of potential reagents to be used as diagnostics, vaccines, immunotherapeutics, or research tools in several branches of biological and biotechnological research. However, the prediction of antibody target sites in proteins using computational methodologies has proven to be a highly challenging task, which is likely due to the somewhat elusive nature of B-cell epitopes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Two recent tools broaden the range of linear methods: While CBtope [142] attempts to predict dis continuous B-cell epitopes from sequential input data, B-Pred [143] utilizes 3D homology models to identify linear epitopes.…”
Section: Epitope Determinationmentioning
confidence: 99%
“…Two recent tools broaden the range of linear methods: While CBtope [142] attempts to predict dis continuous B-cell epitopes from sequential input data, B-Pred [143] utilizes 3D homology models to identify linear epitopes.…”
Section: Epitope Determinationmentioning
confidence: 99%
“…Then DiscoTope ( 1 ) and updated DiscoTope-2 ( 3 ) tried spatial neighbouring definition and surface exposure measurement. Later, PEPTIO introduced spatial attribute of half sphere exposure ( 4 ) and B-pred combined structure quality values with solvent exposure( 5 ). In 2009, we proposed two new parameters, propensity of unit-triangle patches and clustering coefficient in Spatial Epitope Prediction server for Protein Antigens (SEPPA) ( 6 ) to better describe local clustering features of conformational epitope.…”
Section: Introductionmentioning
confidence: 99%
“…L osi et al [ 55 ] reported on the additional benefits of M. tuberculosis -specific antigens to improve upon the interferon (IFN)-γ release assays. New antigens were identified by this approach to distinguish LTBI from active disease [ 56 58 ]. They screened in silico for human leukocyte antigen DR epitopes of M. tuberculosis proteins in 44 clinical strain genomes.…”
Section: Tuberculosismentioning
confidence: 99%